Sanctions for not being read out by the auction office - Wijaya, I Nengah Gowinda (Jurnal Cakrawala Hukum, 2022)
Auction minutes that the Class II Auction Officer does not read will affect their validity. The problem in this paper is about how the validity of the deed is not read out by the auction official, as well as the form of legal protection for the Class II Auction Officer for acceptable sanctions due to the auction minutes not being read out in the implementation of an electronic non-execution auction. This paper aims to analyze the validity of the deed that was not read out by the auction official in the performance of an electronic non-execution auction and a form of legal protection for Class II auction officials. This writing uses a normative juridical method with a statutory and conceptual approach. The study results indicate that the minutes of auction through the internet media have fulfilled the elements contained in Article 1868 of the Civil Code. Legal protection for Class II Auction Officials can be carried out in 2 (two) ways: preventive legal protection, namely by making new rules or improving the provisions of the old laws. Repressive legal protection is to take legal action in the form of an appeal against the Administrative Court or an appeal against the Supreme Court. In the request and cassation, repressive legal protection should be prioritized. How to cite item:Â Wijaya, I. (2022). Sanctions for not being read out by the auction office.Â Jurnal Cakrawala Hukum, 13(2), 164-174. DOI:https://doi.org/10.26905/idjch.v13i2.5896.